Teacher-Student Interaction and Classroom Dynamics: Exploring the Impact on Student Learning (Journal of Universal Science Research, 2023)
Teacher-student interaction plays a crucial role in shaping classroom dynamics and influencing student learning outcomes. This article examines the significance of teacher-student interaction and its impact on classroom dynamics. It explores various factors that contribute to effective teacher-student interaction, including communication styles, feedback strategies, and rapport building. The article also discusses the implications of positive teacher-student interaction on student engagement, motivation, and academic achievement. Understanding the dynamics of teacher-student interaction can inform educators in creating supportive and inclusive learning environments that foster student success.